Response of the Mexican clone of potato 99-39 to potassium in hydroponics and greenhouse - Flores Gutiérrez, Francisco Xavier; Flores López, Román; Mora Herrera, Martha Elena; Franco Mora, Omar (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to determine the effect and optimum dose of potassium in the production of minitubers of the Mexican clone of potato 99-39, experiments were established in July and September 2015, where concentrations of 0 (absolute control), 150, were tested. 250 (commercial control), 350, 450 and 550 mg L-1 in nutrient solution in hydroponic system. The results indicated that the highest plant height and leaf area index were found in the treatments with the highest concentration of K. The dose of 350 mg L-1 of K produced 19% more tubers with a diameter equal to or greater than 15 mm per plant. Than the commercial witness and 194% more than the absolute witness. The second order equation (R2= 0.94) allowed us to estimate that the optimal dose for potato clone 99-39 was 400 mg L-1 potassium, which can produce up to 20.67 minitubers per plant. There was statistical significance in the interaction date x dose for tuber production per plant and for the harvest index, with higher production in july planting than in autumn winter season; conversely, it was found that the harvest index was higher in the autumn-winter season. High concentrations of potassium during the whole crop cycle promoted the production of a greater number of tubers.
Keywords: Solanum tuberosum; nutritive solution; prebasic seed